Kepatuhan Terhadap Firman (Implikasi Ulangan 32 : 44-47 Bagi Pembentukan Karakter Mahasiswa Teologi) - Lestari Situmorang; Selvin Susanto Hura (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2025)
This study examines the implications of Deuteronomy 32:44-47 on the formation of theological students' character, emphasizing obedience to God's commandments. The research highlights the significance of adhering to divine instructions, exploring the consequences of disobedience, and discussing strategies for cultivating obedience. The findings underscore the importance of integrating biblical principles into daily life, fostering spiritual growth, and developing a strong moral foundation among theology students.